Effect of Cross-Linkers on Isabgol Husk-Sodium Alginate Matrix Type Drug Delivery Devices - K. Sharma, Vipin; Bhattacharya, A. (Asian Journal of Chemistry, 2010)
The inherent characteristics of the incorporated polymers e.g., high molecular weight, chain flexibility, nontoxicity, low cost, hydrophilic groups along with high surface tension etc. are required for dosage forms fabrication. Also, the versatility of the other agents as crosslinking agents has their own impact on the release of the incorporated drug and other parameters associated with formulations. In the present study, isabgol husk and sodium alginate were applied as polymeric skeleton for metformin hydrochloride encapsulation in beads form along with calcium chloride/barium chloride as crosslinking agent. The formulations were prepared by orifice-ionic gelation method. The effect of polymer ratio and ionic strength of crosslinking agents was analyzed on drug entrapment efficiency, particle size, swelling index, drug entrapment efficiency, curing time, drug release pattern. The drug-polymer compa-tibility was analyzed by FTIR and DSC. The beads prepared in barium chloride were more spherical and regular in surface than in calcium chloride. The size of the beads was also smaller in barium chloride. Swelling index in phosphate buffer (pH 7.4) of barium crosslinked formulations was significantly different than in 0.1 N HCl for both barium and calcium crosslinked formulations (p < 0.001). More prolonged release was observed in barium crosslinked beads which remained intact after dissolution in simulated intestinal fluid but on the other hand calcium crosslinked formulations were disintegrated completely. FTIR and DSC study revealed the identity of metformin after fabrication in polymeric network.